(NH4)2S2O8‐Mediated Direct Oxysulfonyloxylation of Alkynes with Sulfonic Acids to Access α‐Sulfonyloxyketones. Issue 1 (2nd January 2018) - Zhang, Yang; Tan, Hua; Yue, Chaochao; Liu, Weibing
Abstract: A novel method for the preparation of α‐sulfonyloxyketones via a (NH4 )2 S2 O8 ‐mediated direct oxysulfonyloxylation of alkynes with sulfonic acids is described. This simple yet powerful method allows access to a variety of α‐sulfonyloxyketones with a broad substrate scope. Furthermore, under the stipulated conditions, this methodology demonstrates excellent regioselectivity for some 1, 2‐disubstituted internal alkyne substrates, affording the corresponding α‐sulfonyloxyketones in good yields. Abstract : This protocol is a novel method for preparation of α‐sulfonyloxyketones via a (NH4 )2 S2 O8 ‐mediated direct oxysulfonyloxylation of alkynes with sulfonic acids. This simple yet powerful method for the synthesis of a variety of α‐sulfonyloxyketones has a broad substrate scope. Furthermore, under the stipulated conditions, this methodology demonstrates excellent regioselectivity for some 1, 2‐disubstituted internal alkyne substrates.